Synthesis and characterization of graphene oxide capped sulfur/polyacrylonitrile composite cathode by simple heat treatment. (4th July 2019) - Krishnaveni, K.; Subadevi, R.; Sivakumar, M.; Raja, M.; Prem Kumar, T.
ABSTRACT: A Sulfur/Poly (acrylonitrile) (PAN)/Graphene oxide (GO) hybrid electrode with inter connected structure is prepared through a simple heat treatment. In this process, the formation of a unified poly acrylonitrile /graphene oxide conductive network is accompanied by the uniform loading of sulfur, with a fraction of 52%. The as-prepared S/PAN/GO hybrid delivers an initial capacity of 1424 mAhg −1 at 0.1C. The electrochemical performance of the composite is ascribed to the conductive network designed by interconnected GO and PAN, which supply an unimpeded and uninterrupted path for electron and Li-ion transfer and accommodate the volume variation of sulfur during charge/discharge cycling. Furthermore, the residual functional groups on S/PAN/GO composite can support close contact of the conducting matrix with sulfur and efficiently confine the diffusion of polysulfides. This study gives a green and highly active technique for carbon–sulfur electrode construction for lithium–sulfur batteries. The electrochemical execution improvement can be attributed to the multiple effects of the PAN and GO additive such as conductivity, sulfur distribution, and an active absorber for the reaction products. GRAPHICAL ABSTRACT: